Starch hydrolysis kinetics of intermediate wheatgrass (Thinopyrum intermedium) flour and its effects on the unit chain profile of its resistant starch fraction. Issue 3 (12th April 2019) - Zhong, Yingxin; Mogoginta, Juan; Gayin, Joseph; Annor, George Amponsah
Abstract: Background and objectives: Intermediate wheatgrass (IWG) is an environmentally sustainable perennial crop with potential food applications. This study investigated the starch hydrolysis kinetics of IWG grown in Roseau (IWG‐RS) and Rosemount (IWG‐RM), Minnesota, USA, and the molecular structure of their residual (resistant) starch after 2 hr hydrolysis. Hard red wheat (HRW) and Jasmine rice (JR) were compared to the IWG samples. Molecular size distribution and unit chain profiles of the RS fraction of raw starches after enzymatic hydrolysis were determined with gel permeation chromatography and high‐performance anion‐exchange chromatography, respectively. Findings: Intermediate wheatgrass flour had significantly lower total starch, lower rapidly digestible starch, and higher lipid contents compared to JR and HRW. JR flour had the highest eGI (49.2), with IWG‐RM recording the lowest (40.6). Significant differences were observed in the glucan chain lengths of the RS fraction. JR had the shortest average chain length (DP = 4.75) compared to HRW (DP = 7.46), IWG‐RS (DP = 5.72), and IWG‐RM (DP = 4.85). Conclusions: Intermediate wheatgrass flour had slower starch hydrolysis kinetics compared to JR and HRW flour. The RS fraction of the samples consisted mostly of short chains. The glucan chain length of IWG‐RS fraction was also significantly affected by location. Significance and novelty: Intermediate wheatgrass could potentially be exploited for the preparation of foods with lower glycemic responses.